The Relationship between Trade Openness and Inflation in Selected Developing and Developing Countries - Samira Motaghi; Anahita Saifi; Salah Ebrahimi (فصلنامه پژوهش‌های اقتصادی ایران, 2021)
The aim of this paper was to investigate the relationship between trade openness and inflation in selected developing and developed countries from 1990 to 2017 using a Panel data approach for testing Romer's hypothesis of relationship between inflation index and Trade Openness. The results of the paper show that the Romer hypothesis is rejected in both the studied groups (developed and developing). The results showed that the effect of trade openness on inflation rate was positive and significant in both groups. But the impact of trade openness on inflation has been greater in developing countries. The effect of money supply on inflation was positive and significant in both groups. According to other results of this study, GDP had a significant and negative effect on inflation. Also, the exchange rate has not been a determinant of inflation in developed countries but in developing countries it has had a positive effect on inflation.